Photoelectrochromic device and preparation method thereof - LI MEI; ZHENG JIANMING; YANG SHUWEI; XU CHUNYE (2012)
The invention provides a photoelectrochromic device and a preparation method thereof. The photoelectrochromic device comprises a dye-sensitized electrode, an electrochromic electrode and electrolyte containing a redox couple, wherein the electrolyte is positioned between the dye-sensitized electrode and the electrochromic electrode; the dye-sensitized electrode comprises a first transparent conductive substrate, a porous semiconductor film arranged on the surface of the first transparent conductive substrate, and a dye adsorbed on the surface of the porous semiconductor film; the dye is contacted with the electrolyte; the electrochromic electrode comprises an organic porous electrochromic film, a platinum catalyst layer and a second transparent conductive substrate arranged in turn; and the organic porous electrochromic film is contacted with the electrolyte. The photoelectrochromic device has the advantages of stable cycle performance and short color switching time.